Kewenangan Pengadilan Agama dalam Penyelesaian Sengketa Perbankan Syariah - Juliana Putri; Fitria Andriani (Al-Ahkam: Jurnal Syariah dan Peradilan Islam, 2022)
This study aims to determine and understand the authority of the Religious Courts in dispute resolution and the principles of handling sharia banking disputes. This type of research is a qualitative research with a juridical approach. The results of this study indicate that the enactment of Law No. 3 of 2006 concerning amendments to Law No. 7 of 1989 concerning the Religious Courts has provided a legal umbrella for the application of sharia economic disputes in Indonesia which is the authority of the Religious Courts. Settlement of disputes related to Islamic banking economic activities can be resolved in two ways, namely litigation and non-litigation. In addition, with the change in the legislation of the Religious Courts providing an extension of authority to the Religious Courts, this can be seen from the amendments to the Judicial Law which contained two amendments, in which the first amendment was from Law No. 7 of 1989 to Law No. 3 of 2006. There are 42 articles that have been added and changed, and in the second amendment, namely Law No. 7 of 1989 to Law No. 50 of 2009 there are 24 articles that were added and changed.